Mechanistic evaluation of reactive polymer and crumb rubber synergy in bituminous mixtures: performance-based comparison with SBS modification - Kok, Baha Vural; Yildirim, Furkan; Yalcin, Erkut (Springer, 2026)
In this study, the mechanical performance of hot mix asphalt mixtures modified with crumb rubber (CR) and B2Last (R), an MDI-based reactive polymer, was evaluated and compared with that of conventional SBS-modified mixtures. Mixtures prepared with pure bitumen, 8% CR-modified bitumen (8CR), 8% CR +2% B2Last (R)-modified bitumen (8C2B), and 4% SBS-modified bitumen (4SBS) were investigated. Marshall stability and flow, indirect tensile strength (ITS), indirect tensile stiffness modulus (ITSM), indirect tensile fatigue, and dynamic creep tests were conducted to assess strength, moisture sensitivity, stiffness, fatigue life, and permanent deformation resistance. Comparable performance was generally observed for the 8CR and 4SBS mixtures, whereas the most pronounced improvement was obtained with 8C2B. Marshall stability was increased by 36% and 47% in the 8C2B mixture compared with 8CR and 4SBS, respectively. With the incorporation of 2% B2Last (R) into 8CR, wet and dry ITS values were increased by 24% and 20%, respectively, and the tensile strength ratio was increased to 86%. The stiffness modulus of 8C2B was found to be 134% higher than that of the pure mixture and 68% higher than that of 8CR. The fatigue life was increased from 914 cycles for the pure mixture to 10,408 cycles for 8C2B. Superior rutting resistance was further confirmed by the dynamic creep results, as 8C2B exhibited 7,088 & micro;epsilon permanent deformation after 14,400 cycles and a flow number 14.9 times higher than that of the pure mixture. Overall, the CR-B2Last (R) system was shown to offer a promising alternative to SBS modification for asphalt pavement applications.
Keywords: Crumb Rubber; Reactive Polymer; Polymer Modified Asphalt; Dynamic Creep Resistance; Hot Mix Asphalt